Study of Performance of Shaft output with Rotor-to-Casing Ratios versus Different Vane Angles Adopting Practical Approach on a Novel Multi-Vane Air Turbine (Global Journals of Research in Engineering, 2011)
A concept of using compressed atmospheric air as an alternative to fossil fuel and zero pollution power sources for running light vehicle such as: motorbikes etc.. Here considered vehicle is equipped with an air turbine in place of an internal combustion engine, and transforms the compressed air energy into shaft work. The mathematical modeling shown here is reproduced from author#x2019;s earlier publications on a small capacity compressed air driven vaned type novel air turbine. The effect of different rotor to casing diameter ratios with respect to different vane angles (number of vanes) have been considered and analyzed under specific parametric conditions. The shaft work output is found optimum adopting practical conditions of rotor / casing diameter ratios on a particular value of vane angle (no. of vanes). In this study, the maximum power is obtained as 4.02 kW (5.6 HP) when casing diameter is taken 100 mm, and rotor to casing diameter ratio is kept from 0.70, as the construction of turbine can be fabricated between rotor to casing (d/D) ratio from 0.95 to 0.70 only. It is learnt that the generated power output of 4.02 kW (5.6 HP) is sufficient to run any motorbike.
Keywords: zero pollution; compressed air; air turbine; vane angle; rotor / casing diameter ratio; air-o-cycle